INDEKS KEPUASAN MASYARAKAT (IKM) PADA DINAS PEMUDA DAN OLAHRAGA KOTA BANDUNG TAHUN 2015 - Muslim, Jaliludin (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2016)
The purpose of this study was to measure the Community Satisfaction Index at the Department of Youth and Sports Bandung in 2015. The research method used in this research was survey method with data collection in the form of a structured interview on 150 respondents. Based on the survey results revealed that Community Satisfaction Index survey results at the Department of Youth and Sports Bandung based on nine indicators by PermenpanRB No. 16 of 2014 show a good category with an index value after the conversion amounted to 78.92.